2016
DOI: 10.1063/1.4952958
|View full text |Cite
|
Sign up to set email alerts
|

Scanning thermal microscopy based on a quartz tuning fork and a micro-thermocouple in active mode (2ω method)

Abstract: A novel probe for scanning thermal microscope using a micro-thermocouple probe placed on a Quartz Tuning Fork (QTF) is presented. Instead of using an external deflection with a cantilever beam for contact detection, an original combination of piezoelectric resonator and thermal probe is employed. Due to a non-contact photothermal excitation principle, the high quality factor of the QTF allows the probe-to-surface contact detection. Topographic and thermal scanning images obtained on a specific sample points ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…More recently, Kim et al used SThM implemented in ultrahigh vacuum (UHV), which has the capability of quantitatively mapping temperature fields with high spatial resolution for thermocouple‐based probes. Bontempi et al attached an S‐type thermocouple on the quartz tuning fork (QTF) shown in Figure to replace the optical deflection detection unit of SThM, where shift of natural frequency of QTF could indicate the moment of contact.…”
Section: Instrumentation Of Sthmmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, Kim et al used SThM implemented in ultrahigh vacuum (UHV), which has the capability of quantitatively mapping temperature fields with high spatial resolution for thermocouple‐based probes. Bontempi et al attached an S‐type thermocouple on the quartz tuning fork (QTF) shown in Figure to replace the optical deflection detection unit of SThM, where shift of natural frequency of QTF could indicate the moment of contact.…”
Section: Instrumentation Of Sthmmentioning
confidence: 99%
“…Thermocouple probe integrated on a quartz tuning fork (QTF).The arrows point out to the thermocouple junction, which is made of Pt and Pt‐Rh10% wires with a tip diameter of ≈1.27 μm. Reproduced with permission . Copyright 2016, American Institute of Physics.…”
Section: Instrumentation Of Sthmmentioning
confidence: 99%
See 1 more Smart Citation
“…Devices have been electro-thermally characterized by determining the temperature coefficient of the resistors (TCR = 0.00185 K −1 ) and by measuring temperature vs. power consumption using the SThM thermocouple probe presented in [2]. Figure 3 presents a scan result on the 1st design (temperature and topography maps) at 11 mW power supply and the temperature at the center of the device versus power.…”
Section: Resultsmentioning
confidence: 99%
“…Derived from Atomic Force Microscopes, they are able to operate in two complementary modes, either in passive mode for surface temperature measurements [1], or in active mode for thermal parameters estimation (thermal conductivity or diffusivity typically) [2]. However, none of these modes are reliable yet due to the complexity of the thermal interaction between the probe tip and a sample surface.…”
Section: Introductionmentioning
confidence: 99%